Factores que influyen en adherencia al tratamiento antituberculoso en pacientes atendidos en Huaquillas de la provincia El Oro - Bazán Correa, Jennifer Carolina (2021)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, a bacterium that almost always affects the lungs, although it also affects other organs to a lesser extent, it is a public health problem where various factors intervene that influence adherence to treatment for compliance with therapy. This research was carried out with the objective of determining the factors that influence adherence to antituberculous treatment in patients treated in Health Units of the El Oro province. It was carried out with a descriptive, correlational, cross-sectional and retrospective quantitative approach. The sample consisted of 29 patients with a diagnosis of tuberculosis in the health units of Huaquillas who met the criteria, a survey was used for data collection where the results of the analysis show 66% patients adhered to the treatment with a predominance of the male gender. , 53% were older than 40-64 years and in the group of 15-19 years 40% those who did not adhere, when determining the factors that influence adherence, 74% had completed secondary school, 100% received medication In the health unit and it is within a short distance, 100% receive family support during treatment, with respect to work activity, 53% do not have a job and 74% did not present satisfaction with the care provided. Keywords: tuberculosis, age groups, health personnel